PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR TEKNIK DASAR MENGGIRING BOLA PADA SISWA KELAS VIII K SMP NEGERI 1 MENGWI TAHUN PELAJARAN 2018/2019 - I Komang Adi Palgunadi; I Gusti Ngurah Baskara Putra (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
This study aims to improve learning outcomes for basic techniques of dribbling in class VIII K students of SMP Negeri 1 Mengwi in the 2018/2019 academic year. This research is a classroom action research, namely the teacher as a researcher where the implementation of this research is carried out in 1 cycle consisting of planning, implementing, evaluating, and reflecting. The subjects of this study were students of class VIII K of SMP Negeri 1 Mengwi in the 2018/2019 academic year, totaling 34 students, 16 male students and 18 female students. The research data were analyzed using descriptive statistics. The results of the research data analysis showed that the average value of the two evaluators was 89.70%, and the percentage of completeness of the basic techniques of dribbling learning outcomes in class VIII K students of SMP Negeri 1 Mengwi in the academic year 2018/2019 was 94.12%. The results of learning the basic techniques of dribbling with the inner foot can be increased through the application of the TAI type cooperative learning model for class VIII K students of SMP Negeri 1 Mengwi in the 2018/2019 academic year. Therefore, the researcher suggests physical education teachers to use the TAI learning model because it can improve learning outcomes for the basic techniques of dribbling with the inner foot.